Improving Vocabulary Mastery Through Storytelling Methods Using Picture Story Books at TKIT Al-Jabar Bekasi - Rayhan Saputra; Lia Kuniawati; Wening Rahayu (Bulletin of Early Childhood, 2025)
This research was motivated by the low vocabulary mastery of group B1 children at TKIT Al-Jabar Bekasi. The purpose of this study was to improve children’s vocabulary skills through the storytelling method using picture storybooks. This study employed Classroom Action Research (CAR) conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 12 children in group B1. Data were collected through observation, interviews, and documentation, and analyzed using descriptive quantitative and qualitative approaches. The results showed a significant improvement in children’s vocabulary skills, from 25.60% in the pre-cycle to 65.00% in cycle I, and reaching 95.83% in cycle II. Thus, the research success indicator of 70% was achieved. The study concludes that the storytelling method using picture storybooks is effective in enhancing the vocabulary mastery of early childhood learners.